Implementation of Green Practices on Room Attendant at Sofitel Bali Nusa Dua Beach Resort - I Komang Triartha Pramana; Ni Nyoman Sri Astuti; Lien Darlina; I Ketut Astawa (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: The purpose of this study was to analyze whether the room attendant at Sofitel Bali Nusa Dua Beach Resort had implemented green practices and to find out which indicators need to be improved and maintained in implementing green practices. Research methods: This study uses descriptive statistical analysis techniques with data collection methods by means of observation, interviews, questionnaires, and documentation. The method of determining the informants using purposive sampling method with the number of informants 33 people from room attendant employees. Findings: The room attendant has implemented green practices very appropriately In the implementation of green practices, there are 3 green practices variables with 9 indicators, where in implementing this program there are 2 indicators that need to be improved, namely the first use of reused bed linen in hotel rooms and secondly the use of reused towels in bathrooms. In an effort to improve the 2 indicators of green practices, the author suggests using or multiplying decorative ornaments containing words or writings that ask guests to reuse bed linen and towels in the hotel room. Implication: With the implementation of green practices in room attendants, it is expected to reduce the impact of environmental damage that can be caused by the hotel industry.